North-North migration and agglomeration in the European Union 15 - Daniela Costa; Maria Jose Rodriguez (Banco de México, 2020)
This paper provides evidence on migration of workers within the European Union 15 (EU15), disaggregated by occupation. Using the European Labor Force Survey from 1983-2013, we find that in high-educated occupations, EU15 workers move to EU15 countries where their occupation is relatively more abundant among natives. This is at odds with traditional models of migration. We argue that a different framework is more suitable to analyze migration flows across highly educated highincome countries. In particular, we develop a model with external economies of scale that generates agglomeration of highly educated labor. The main implication of the model is that workers of higheducated occupations migrate to countries that are abundant in labor of their same occupation, in accordance with the data.
Keywords: F12; F15; F22; E2; 330; North-North Migration; Occupation; Agglomeration; European Union